The Role Of E-Government In The Face Of Administrative Corruption - Adnan Sadiq, Haider; Mohammed Obaid, Ruqaya (Opción, 2019)
The world is witnessing rapid growth in knowledge, cultural and informa- tion data, and e-government is one of the most important and contemporary interfaces of information technology responsible for economic growth and sustainable human development, and the administrative corruption in Iraq, has become a serious phenomenon that does not hinder the work of e-gov- ernment alone, Rather, paralysis occurs in the process of construction, de- velopment and economy, which makes the state unable to meet the challeng- es of reconstruction and building the necessary infrastructure for its growth at the political, economic, financial, social and cultural levels.